PERANCANGAN APLIKASI BELAJAR DENGAN METODE TRIVIA BERBASIS GOOGLE ASSISTANT BAGI PENYANDANG DISABILITAS TUNA NETRA - Aulia Andinia (2020)
This mobile based application called "Natasha Bot" is a virtual learning media aimed at people with disabilities especially blind people. Natasha Bot contains questions about subjects in schools designed for elementary school students in grade 6 in the form of guessing or trivia. The system and infrastructure of special learning activities for people with disabilities that have been facilitated by the government are felt to be lacking because there are still some problems that arise such as the inconvenience of students with disabilities in the learning environment because they feel different and also teachers in inclusive schools who have not been equipped with special skills or techniques in learning for people with disabilities. The Natasha Bot application comes as an innovation that utilizes open source technology from Google is designed to make students with disabilities especially the blind feel comfortable in learning activities because there are voice features in Natasha Bot that make it a two-way communication between the student and Natasha Bot therefore, Natasha Bot also acts as a virtual friend as well as a media learn. Natasha Bot comes with Artificial Intelligence technology and is designed using the Google Assistant framework with the method of trivia or guessing and Google Sheets as a database or storage media. This research uses the design thinking method. Natasha Bot is expected to help advance the world of education, especially for people with disabilities with visual impairments with a more teachable and psychological approach.